Front Porch Revolution: Resilience Space, Demonic Grounds, and the Horizons of a Black Feminist Otherwise. - McTighe, Laura; Haywood, Deon (Signs: Journal of Women in Culture & Society)
The article focuses on Women With A Vision (WWAV) which is black feminist collective walked into their first home and to improve the lives of marginalized women and their communities by addressing the structural conditions that hinder their health and well-being. It mentions isolating black women from necessary social services and criminalizing them for this victimization. It also mentions goal of political empowerment and social justice.